PENERAPAN TOKEN EKONOMI DALAM MENURUNKAN KECANDUAN GADGET PADA ANAK - Putri Dwi Priskova; Lubna Nafahat; Muhammad Jamaluddin (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
In the current digital era, all individuals are familiar with technology called gadgets. Gadgets have already become an inseparable part of everyday life because they can facilitate human work. In fact, for children, gadgets are interesting because of the various things that are in it. Apart from being useful, gadgets can also have a negative impact if used excessively and can even cause addiction in children. Token economy is one of the suitable methods because this model is considered appropriate to be applied at the age of children because there is a reward agreement desired by the subject. The subject of this research is a child in Lamongan Regency. This study uses a quantitative method, namely the Wilcoxon Test. The purpose of this study was to reduce the duration of gadget use and reduce his maladaptive behaviour when in contact with gadgets. The results showed that the token economy method was effective in reducing gadget addiction in children.